A subordinação da agricultura ao capital: transformações da produção agrícola na sociabilidade capitalista - Martins, Samyra Santos (2020)
The present study aims to investigate the transformations of agricultural production in the capitalist society, observing the process of subordination of agriculture to capital. The expropriation of the peasantry from its land base and the transition from feudal and clan ownership to private ownership, made agriculture increasingly indispensable for capital accumulation. Since its origin, agriculture has not focused on the production of goods, but this occurs from the separation of direct producers from their means of production, driven by rural wage labor and deprived of any conditions of subsistence and production. The genesis of these transformations occurs from the primitive accumulation of capital and is intensified with the agricultural mechanization arising from the Industrial Revolution. Thus, adopting a historical-critical perspective as a methodological procedure, a bibliographical and documentary survey of Marxian and Marxist works was carried out that point out the transformations in agricultural production. Among the authors used as reference, it is worth mentioning: K. Marx, F. Engels, V. Lenin, R. Luxemburgo, Kautsky, among others. For that, we investigated in the first moment the difference of work and agriculture in the creation of use value versus exchange value, aiming to elucidate the function of work and agriculture. In the next section, we investigate the historical conditions of subordination of agriculture to capital, from the genesis of primitive accumulation to the Industrial Revolution, highlighting the transformation of the natural economy in the face of the expropriations of the peasants, the destruction of the rural domestic household trade, the leasing of land, mechanization in the field and spoliation of the colonies. Finally, we investigated agriculture in the imperialist phase, in view of the need for capital accumulation, showing how this process intensifies the relations of expropriations in the countryside from the diffusion of technological packages of the "Green Revolution", production of "biofuels" etc. From this investigation, we found that the subordination of agriculture to capital is a permanent process of transforming natural economies into capitalists, being carried out through new-old forms of expropriation of peasants in order to meet the uncontrollable desire of capital for more- worth.